Weak Governance, Divided Residents: The Development of Gated Communities in Guatemala City - Dalby, Laura (Université d'Ottawa / University of Ottawa, 2013)
This thesis asks the question: how can one describe the development of gated communities in Guatemala City? It collects and analyzes data on gated communities in Guatemala City in order to explore the nature of their development in a violent geographical region, which has also been neglected by the academic community. It argues that the development of gated communities in Guatemala City does not fit the mutually exclusive ‘security’ argument as scholars have made. Instead, a mixture of economic factors, social status, weak governance, and security concerns are involved as large private corporations draw upon security-related fears, unregulated development of real estate and weak governance, resulting in a disorganized model of spatial organization. This study adds to the growing body of literature on gated communities by laying the groundwork needed to fill the gap that currently exists in Central America.
Keywords: Weak Governance; Gated Community; Guatemala City; Central America; Habitus; Security; Neo-Liberalism; Social Status; Fear; Public-Private Space; Spatial Organization